2005
DOI: 10.2174/138945005774574498
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Agents for the Treatment of Advanced Renal Cell Carcinoma

Abstract: Renal cell carcinoma (RCC) is a highly treatment-resistant tumor type; however, advances in elucidating the molecular pathophysiology underlying RCC has led to the identification of promising targets for therapeutic intervention. In clear-cell RCC, mutations to the von Hippel-Lindau (VHL) gene results in the up regulation of many proteins necessary for tumor growth and survival--such as vascular endothelial growth factor (VEGF), basic fibroblast growth factor (bFGF) and platelet derived growth factor (PDGF), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(57 citation statements)
references
References 0 publications
2
53
0
2
Order By: Relevance
“…In addition, the activated MAPK or increased levels of MAPK expression have been detected in a variety of human tumors (Oka et al 1995, Sivaraman et al 1997, Hoshino et al 1999, Kim et al 1999, Ahmed et al 2002, Satyamoorthy et al 2003, Liang et al 2005, Takata et al 2005. Thus, the MAPK signaling pathway is a potential target in cancer therapy (Duesbery et al 1999, Tecle et al 1999, Fang & Richardson 2005, Staehler et al 2005.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the activated MAPK or increased levels of MAPK expression have been detected in a variety of human tumors (Oka et al 1995, Sivaraman et al 1997, Hoshino et al 1999, Kim et al 1999, Ahmed et al 2002, Satyamoorthy et al 2003, Liang et al 2005, Takata et al 2005. Thus, the MAPK signaling pathway is a potential target in cancer therapy (Duesbery et al 1999, Tecle et al 1999, Fang & Richardson 2005, Staehler et al 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Additional investigations revealed that ZD6474 blocked the downstream signaling pathways including extracellular signalregulated kinase (ERK) signaling in EOL-1 cells (Figure 1b). Further studies examined the antileukemic activity of AZD6244 (ARRY-142886), 3 a novel inhibitor of mitogen-activated protein kinase /ERK signaling. The drug synergistically enhanced the .…”
mentioning
confidence: 99%
“…[1][2][3][4] Clinical trials with VEGF inhibition in a variety of malignancies are ongoing. The best-studied and most advanced approach to VEGF inhibition is the recombinant humanized monoclonal antibody bevacizumab (BV -1 mM) or control diluent.…”
mentioning
confidence: 99%
“…In single-agent EGFR inhibitor trials, gefitinib (a selective EGFR TKI) and cetuximab (a recombinant mousehuman mAb) were administered as monotherapy. Neither agent demonstrated a complete or partial response (Staehler et al, 2005). In a randomized phase II trial, clear cell RCC patients received either bevacizumab or bevacizumab plus the EGFR inhibitor erlotinib.…”
Section: Targeting Egfrmentioning
confidence: 99%